2016
DOI: 10.14202/vetworld.2016.811-819
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with Cryptosporidia, Eimeria, and diarrhea in smallholder dairy farms in Mukurwe-ini Sub-County, Nyeri County, Kenya

Abstract: Aim:This study was undertaken to determine the household, calf management, and calf factors associated with the occurrence of Eimeria, Cryptosporidia, and diarrhea in pre-weaned calves reared in smallholder dairy farms in Mukurwe-ini Sub-County of Nyeri County, Kenya. In addition, the study also evaluated factors associated with average daily weight gain in the same pre-weaned calves.Materials and Methods:A total of 112 newborn calves (63 males and 49 females) on 111 farms (1 set of twins) were followed for 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
3
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 17 publications
0
8
3
6
Order By: Relevance
“…The prevalence of Eimeria spp. in this study was lower than previously reported [1,2,4,6,17]. These differences may be attributed to calf age, breed, the sampling time, and geographical location.…”
contrasting
confidence: 81%
“…The prevalence of Eimeria spp. in this study was lower than previously reported [1,2,4,6,17]. These differences may be attributed to calf age, breed, the sampling time, and geographical location.…”
contrasting
confidence: 81%
“…and Giardia spp. ranged from 11% to 15.6% [6131831] and 9.34% to 29%, respectively [183133]. In the present study, protozoans were the most common causative agents.…”
Section: Discussionmentioning
confidence: 68%
“…The prevalence of Eimeria spp. was reported to range from 21.2% to 83.67% [313182039], while that of Cryptosporidium spp. and Giardia spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Improved animal welfare reduces the stress level in calves, enhances immune function and subsequently increases weight gain [ 5 ]. There have been several reports of calf growth, morbidity, and mortality on smallholder dairy farms in Kenya [ 28 , 29 ]. However, to the best of our knowledge, there has never been an assessment of calf comfort or its indicators on smallholder dairy farms in Kenya or other developing countries.…”
Section: Introductionmentioning
confidence: 99%